EARLY DEVELOPMENT OF AL, CA, AND NA COMPOSITIONAL GRADIENTS IN LABRADORITE LEACHED IN PH 2 HCL SOLUTIONS - Nesbitt H.W.; Skinner W.M. (My University, 2001)
Labradorite reacted with HCl solution (pH = 2.0) develops leached layers extending to about 500 #9 depth after 12 h leaching, and to 1500 #9 depth after 143 h leaching. Accurate Al, Ca, and Na compositional depth profiles were measured using x-ray photoelectron spectroscopy (XPS), with compositional accuracy of about 10% and depth resolution of about 50 #9. XPS analyses of pristine K-feldspar and labradorite surfaces yield Ca, Al, Si, and O analyses within about 5% of electron microprobe results. Alkali element analyses are inaccurate due to preferential sputtering or mobility induced by fracture. The accurate compositional depth profiles yield well constrained diffusion coefficients and moving boundary velocities for Ca and Al. Na, Ca, and Al compositional gradients change character after about 2 days of leaching, from a convex upward hyperboloid to a sigmoid shape. Thereafter, the feldspar diffusion front is clearly separated from the surface (where silica dissolution occurs), with the diffusion front migrating into the feldspar at about 4 x 10-11 cm/s. Al diffuses down the compositional gradient at about 2.5 x 10-17 cm2/s and Ca diffuses almost twice as fast (4.0 x 10-17 cm2/s). The solution-solid interface and active leaching zone are separated (after 2 days) by a Si-rich zone virtually devoid of Na, Ca, and Al. Diffusion rates through this Si-rich overlayer may be very rapid and approach rates observed in aqueous solutions. Diffusive release of Ca and Al from labradorite cannot be modelled accurately with mathematical solutions where diffusion through homogeneous media is assumed. During leaching, Ca and Al apparently diffuse by ''jumping'' to, and residing on, previously vacated structural sites of the feldspar. The probability of Ca and Al migrating towards solution consequently is greater than their probability of migrating towards pristine plagioclase, primarily because there are many more ''vacant'' sites in the leached zone than in pristine plagioclase. Diffusion is inhomogeneous and ''impeded'' in the direction of the pristine feldspar.